The use of E-Payment Method and Its Influences on Student’s Payment Transaction Method in Jayapura City - Indra Eka Wardana Toii; Xenia Irene Sandy Landjang; Rizka Cintya Edwar; Alfani Laura Harikedua; Nur Mila Sari (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
The purpose of this study is to describe the perspective of students in Jayapura city using the e-payment method in every payment transaction. The method used in this study is a quantitative method. The respondents selected were students who were carrying out lecture activities in Jayapura city. The results of the study found and concluded that the e-payment method is a new breakthrough in payment transactions that affect students who carry out lecture activities in Jayapura city. With the e-payment method, students in Jayapura city can make non-cash payment transactions and can reduce the use of cash as a means of payment. The results of this study indicate that the e-payment and payment transaction variables show valid and reliable results. The coefficient of determination value of the research results shows the ability of the e-payment variable in its influence on payment transactions by 57% and the rest are variables not discussed in this study. The results of the regression equation Y = 3.491 + 0.786X show a positive direction coefficient result from e-payment on payment transactions and the hypothesis results show positive and significant results of e-payment on student payment transactions in Jayapura city, in the sense that with the existence of the e-payment payment method, students in Jayapura are much freer and much more motivated to make purchases in this case referring to payment transaction activities that are more in line with a practical lifestyle.